Electrospinning and spinning techniques combined for novel mixed matrix hollow fiber membranes: Structural analysis - Junoh H.; Jaafar J.; Mohamed H.; Pin Jern K. (Elsevier Ltd, 2025)
This study experimentally and theoretically explores the feasibility of combining electrospinning and spinning methods in delivering high performance hollow fiber membrane structure especially for biogas separation. In this preliminary study, the zeolitic imidazolate framework-8 (ZIF-8) crystals were successfully synthesized, and the electrospun fiber of polysulfones (PSF)/ZIF-8 was successfully achieved via the electrospinning process. Interestingly, the images from scanning electron microscopy (SEM) showed a consistent arrangement of ZIF-8 electrospun fibers at the lumen side of the PSF/ZIF-8 hollow fiber membrane. This phenomenon was believed to be due to the bore fluid type, which consisted of N-methyl-2-pyrrolidone (NMP) and water (H2O), which affected the backing layer of hollow fiber. Moreover, this study might provide insight into the effect of bore fluid on the position of electrospun ZIF-8 fibers, and further study can be conducted to confirm the feasibility of these membranes being used in the applications such as for gas separation processes. ? 2024 Elsevier Ltd. All rights reserved.